STUDI PENILAIAN KONDISI DAS DAN IMPLIKASINYA TERHADAP FLUKTUASI DEBIT SUNGAI (STUDI KASUS PADA SUB DAS JANGKOK PULAU LOMBOK) - Suhartanto, Ery; Priyantoro, Dwi; Itratip, Itratip (Jurnal Teknik Pengairan, 2012)
In the last two decade, there has been a dramatically land use changes in the sub-catchment area of Jangkok, Lombok, from forest toward agroforestry. The results of study show that 17.32% of upper stream of Sub-Jangkok due to land use changes from 1995 to 2010 has not been degraded or still good quality catchment indicated by the following variables: coefifient C = 0.16 and potential soil erosion of 6.0 t ha-1 year-1. The C = 0.16 means that the was only 16 % of rainfall undergo run off and the rest of 84% goes to infiltration to enrich ground water. According to the natural erosion in the region which is about 5.75 t/ha/ year, the erosion index was 0.59 or less than 1 classified as low incident. Overall, the land use changes in upper stream of sub-catchment of Jangkok was not significantly correlated to the river-water recharge fluctuation. This was confirmed by the RRC (1.67) and MD (0.21 m3/sec) resulted from 1992-1996. In the next seven years (1997-2003) the RRC and MD were 2.47 and 0.35 m3/sec respectively. In 2004-2010, the RRC and MD were 2.0 and 0.25 m3/sec. However, there were slightly decline of river-water recharge (0.03 m3/sec/year) as well as rainfall (14.64 mm/year) and daily rainfall much as 10 days within the last 10 years.Keywords: land use changes, catchment, runoff, erosion, water recharge.